How Does Destination Social Responsibility Influence Support for Educational Tourism Development? The Mediating Roles of Perceived Benefits and Quality of Life - Bih, Renee Chey (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Although there is a rise in the studies on educational tourism, no investigation has done on the impact of educational tourism destination social responsibility (DSR) on residents The purpose of this study is to examine the relationships between DSR, perceived benefit (BEN), quality of life (QOL), and support (SUP) for the development of educational tourism. The mediating roles of perceived benefits and QOL of the residents were examined in this study and it was analyzed with a sample of 326 respondents staying in Famagusta, North Cyprus. The outcome of this investigation reveals that DSR has direct positive effects on BEN and QOL as well as BEN and QOL have direct positive effects on support. Besides that, perceived benefit and quality of life played important roles in mediation in the relationship between DSR and support. This thesis provides the implications for decision-makers, planners, and practitioners along with the results obtained based on the theory of social exchange. Keywords: Tourism Development, Destination Social Responsibility, Perceived Benefit, Quality of Life, Residents‟ Support,Educational Tourism, North Cyprus

ÖZ: Eğitim turizmi ile ilgili çalışmaların sayısında artış olmasına rağmen, eğitim turizminde destinasyonun sosyal sorumluluğunun (DSS) bölge sakinleri üzerindeki etkisine dair araştırmalar bulunmamaktadır. Bu çalışmanın amacı DSS, algılanan fayda (FAY), yaşam kalitesi (YK) ve eğitim turizminin gelişimine yönelik desteğin (DES) arasındaki ilişkileri incelemektir. Bu çalışmada, algılanan fayda ve yaşam kalitesi aracı değişkenler olarak ele alınmıştır. Araştırma kapsamında, Gazimağusa, Kuzey Kıbrıs‟ta yaşayan 326 katılımcıya anket uygulanmıştır. Araştırma sonucunda elde edilen bulgulara göre, destinasyonun sosyal sorumluluğunun algılanan faydalar ve yaşam kalitesi üzerinde pozitif etkileri olduğu saptanmıştır. Aynı zamanda, algılanan faydalar ile yaşam kalitesinin eğitim turizminin gelişimine yönelik destek üzerinde olumlu etkileri olduğu bulunmuştur. Ayrıca, algılanan fayda ve yaşam kalitesi, DSS ile eğitim turizminin gelişimine yönelik destek arasındaki ilişkide aracı olarak önemli roller oynamaktadır. Bu tez, sosyal değişim kuramı temelinde elde ettiği sonuçlar ile birlikte karar vericiler, planlamacılar ve uygulayıcılar için uygulamaya yönelik tavsiyeler sunmaktadır. Anahtar Kelimeler: Turizm Gelişimi, Destinasyonun Sosyal Sorumluluğu, Algılanan Fayda, Yaşam Kalitesi, Bölge Sakinlerinin Desteği, Eğitim Turizmi, Kuzey Kıbrıs
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Assoc. Prof. Dr. Ali Öztüren.
Keywords: Tourism; Tourism--Educational Tourism--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Students--Travel--Foreign study--Tourism; Tourism--Study and teaching (Higher)--Cyprus, North; Hospitality industry--Study and teaching (Higher)--Cyprus, North; Tourism Development; Destination Social Responsibility; Perceived Benefit; Quality of Life; Residents‟ Support; Educational Tourism; North Cyprus